Tinjauan Yuridis terhadap Perma No. 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana - Martha Eri Safira (Justicia Islamica, 2017)
The Supreme Court made a new breakthrough in the civil justice system with the issuance of Supreme Court Regulation No. 2 Year 2015 on the Procedure for Settlement of Simple Lawsuits. Disputes that can be resolved are default or breach of promise disputes with a maximum dispute value of Rp. 200,000,000.00 (two hundred million rupiah). Resolved with a maximum grace period of 1 month (25 working days). Every trial that takes place must be attended by both parties and or their attorneys in dispute. The judge who examines the case is a single judge, not a panel. When examined from the principles of civil procedural law, both in the HIR, Law No. 5 of 2004 concerning the Supreme Court, and Law No. 48 of 2009 concerning Judicial Power, there are many deviations from the principles of civil procedural law.